Weak Forms of $μ(σ_1,σ_2)$-continuity for Multifunctions (European Journal of Pure and Applied Mathematics, 2025)
A new class of continuous multifunctions between a generalized topological space and a bitopologicalspace, namely upper (lower) weakly $μ(σ_1,σ_2)$-continuous multifunctions, has been defined and studied. Moreover, several characterizations and some properties concerning upper weakly $μ(σ_1,σ_2)$-continuous multifunctions and lower weakly $μ(σ_1,σ_2)$-continuousmultifunctions are established. Furthermore, the relationships between almost $μ(σ_1,σ_2)$-continuity and weak $μ(σ_1,σ_2)$-continuity are considered.
Keywords: upper weakly $μ(σ_1,σ_2)$-continuous multifunction; lower weakly $μ(σ_1,σ_2)$-continuous multifunction